Elopement of adolescent Filipinos in rural areas - Dy, M. R. (2003)
This study explored the cases of elopement of a selected group of rural adolescent females. Personal characteristics, parental characteristics, engagement in risk behaviors, and relationship characteristics that could have influenced the elopement were studied. Impact of the elopement on the respondents' lives was also considered. The nine respondents from Alaminos, Laguna, aged 16-20 years old underwent an in-depth interview about, their elopement cases. The findings of the study were the following: a) age and level of educational attainment seemed to be influential factors contributing to the elopement since most were 16-17 year old at the time of elopement and majority have not finished their secondary education; b) most of the parents whose daughter eloped had no knowledge of the relationships since the respondents were afraid of their parents' anger or disapproval; c) most of the respondents tried out drinking as compared to smoking and taking drugs but this does not seem related to the elopement, and d) all had experienced early relationships, most had short lengths of courtship, and most had short relationships before the elopement occurred. Further, most of the respondents eloped on a spur-of-the-moment decision. The elopement has given rise to various social, sexual, financial, and relationship adjustments in the respondents. Further studies on a wider group of adolescents females and their male partners in different settings can enrich the understanding of elopement, its impacts, and the factors influencing in the Philippine setting.
Keywords: Elopement